Drug-resistant cancer cell-derived exosomal EphA2 promotes breast cancer metastasis via the EphA2-Ephrin A1 reverse signaling - Gao, Zicong (Cell Death Dis, 2021)
Tumor metastasis induced by drug resistance is a major challenge in successful cancer treatment. Nevertheless, the mechanisms underlying the pro-invasive and metastatic ability of drug resistance remain elusive. Exosome-mediated intercellular communications between cancer cells and stromal cells in tumor microenvironment are required for cancer initiation and progression. Recent reports have shown that communications between cancer cells also promote tumor aggression. However, little attention has been regarded on this aspect. Herein, we demonstrated that drug-resistant cell-derived exosomes promoted the invasion of sensitive breast cancer cells. Quantitative proteomic analysis showed that EphA2 was rich in exosomes from drug-resistant cells. Exosomal EphA2 conferred the invasive/metastatic phenotype transfer from drug-resistant cells to sensitive cells. Moreover, exosomal EphA2 activated ERK1/2 signaling through the ligand Ephrin A1-dependent reverse pathway rather than the forward pathway, thereby promoting breast cancer progression. Our findings indicate the key functional role of exosomal EphA2 in the transmission of aggressive phenotype between cancer cells that do not rely on direct cell–cell contact. Our study also suggests that the increase of EphA2 in drug-resistant cell-derived exosomes may be an important mechanism of chemotherapy/drug resistance-induced breast cancer progression.